2018
DOI: 10.32674/jis.v8i1.160
|View full text |Cite
|
Sign up to set email alerts
|

Academic Adaptation Among International Students from East Asian Countries: A Consensual Qualitative Research

Abstract: This study used a consensual qualitative research method to explore academic adaptation experiences of international students (N = 13) from East Asia countries at a U.S. university. The analysis yielded five domains from the data (challenges, feelings, strategies, suggestions, and self-reflections). Implications for college counselors, university administrators, and future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 24 publications
2
23
0
2
Order By: Relevance
“…Regarding oral communication, similar to previous research, difficulties with oral communication affected participants' sense of confidence and self-esteem and resulted in negative emotions and even stress (Kuo, 2011;Li et al, 2018;Mitchell et al, 2017). These negative emotions may lead to a decreased sense of social satisfaction and belonging, and overall student engagement (Horne et al, 2018).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Regarding oral communication, similar to previous research, difficulties with oral communication affected participants' sense of confidence and self-esteem and resulted in negative emotions and even stress (Kuo, 2011;Li et al, 2018;Mitchell et al, 2017). These negative emotions may lead to a decreased sense of social satisfaction and belonging, and overall student engagement (Horne et al, 2018).…”
Section: Discussionsupporting
confidence: 64%
“…Rosenthal, Russell, and Thomson (2008) found that, among 979 international students surveyed, 24% of Asian students reported having difficulties in written English and 22% in spoken English as well as a high level of stress. Li et al (2018) reported frequent references to challenges related to English proficiency, connections with locals, course readiness, and time management among 13 East Asian international students studying in the US. A study by Kuo (2011) explored language challenges faced by international graduate students in the United States.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars such as Helfer and Drew (2019), however, refer to academic failure experiences of postgraduate students as "unhappy, discouraged or disappointed" (p. 512), stressed, exhausted and burn out (Cornér et al, 2017) or experiencing low satisfaction and engagement levels (Löfström & Pyhältö, 2014) due to an ineffective supervision process and other related issues pertaining to international postgraduate students. The most common challenge faced by international postgraduate students is limited English proficiency skills in writing, reading and speaking (Alsahafi & Shin, 2017;Li et al, 2018). Thus, international postgraduate students in Malaysia acknowledged that they might take up to three hours to read and understand one journal article because the vocabulary and terminologies used in some academic journals created complications for them in comprehending key arguments of the article (Kaur & Sidhu, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…International scholarship in China has been enhancing the political, diplomatic and economic ties between China and those countries as well as promoting the exchange of culture, education and personnel. With 33 provinces in China [10], the Ministry of Education in China lists few provinces that rank higher than others in terms of hosting international students in the country. Table 1 shows top 10 provinces with the highest number of international students.…”
Section: Background Of China's Inflow Of International Students Frommentioning
confidence: 99%